Studi Komparasi Konduktivitas Konduktor Tembaga Bentuk Serabut Dan Pejal Dengan Media Air Tawar (H2O) - Rita Hariningrum; Sukarno Budi Utomo (Universitas Ivet, 2021)
Choosing a good conductor is still a problem. This is due to many factors including the cost and time required as well as expensive facilities but so far to determine the quality of materials accurately and effectively in a simple way has not been carried out except through complex laboratory tests such as through photo electrons and mechanical tests of materials which are expensive. . It is possible by the principle of heat dissipation in the conductor which as an alternative to the new test method is estimated to be low cost. Tests with the heat dissipation method on the conductor can be seen macroscopically that the conductivity is very influential in the conductor because it involves the speed of electrons contained in the conductor, if the conductor has a small resistance then the conductor has a high conductivity speed or in other words that the conductor has a high resistance. Small is a good conductor material used as a conductor.